2005
DOI: 10.1149/1.1825954
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Treatment of Synthetic Graphite under Argon and Effect on Li-Ion Electrochemistry

Abstract: The novel use of heat-treatment in flowing Ar to systematically affect particle and crystallite dimensions of synthetic graphite LK-702 is reported. Samples were characterized by percent mass loss, X-ray powder diffraction, scanning electron microscopy, Brunauer-Emmett-Teller ͑BET͒ surface area, and methylene blue adsorption surface area measurements. The treated graphites were studied as possible electrode materials for Li-ion cells. The BET and methylene blue surface areas increased for treatment times up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…12,13 It has been previously established that the 3.2 V plateau is associated with Ag reduction and the 2.7 V and 2.4 V features correspond to V reduction. 1,12,13 The incoming lithium ions simultaneously reduce and displace the Ag + ions which are bound in the oxygen layers of the Li x Ag 2 V 4 O 11 structure. 14 While these sites are large enough to accommodate atomic silver, in the event that the silver is reduced while the lithium intercalates into a separate site, there exists strong evidence that the silver atoms come out of the host structure and crystallize onto the surfaces of the particles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 It has been previously established that the 3.2 V plateau is associated with Ag reduction and the 2.7 V and 2.4 V features correspond to V reduction. 1,12,13 The incoming lithium ions simultaneously reduce and displace the Ag + ions which are bound in the oxygen layers of the Li x Ag 2 V 4 O 11 structure. 14 While these sites are large enough to accommodate atomic silver, in the event that the silver is reduced while the lithium intercalates into a separate site, there exists strong evidence that the silver atoms come out of the host structure and crystallize onto the surfaces of the particles.…”
Section: Resultsmentioning
confidence: 99%
“…Extensive electrochemical characterization of the Li/SVO system has been carried out by several other groups. [1][2][3] Mechanistic studies of this multistep reduction have also been conducted and have identified the formation of silver metal in the early stage of the reaction, through the use of X-ray powder diffraction and scanning electron microscopy/ energy-dispersive spectroscopy ͑SEM/EDS͒. 4,5 However, electrochemical and X-ray diffraction measurements yield only average structural changes related to lithium insertion.…”
mentioning
confidence: 99%
“…But if the measured domain sizes could be considered equivalent to the dimensions of discrete crystallites, they could be used to estimate the ASA. Thus in the absence of suitable alternatives, in practice these parameters are either used directly for materials comparison and selection [8][9][10][11][12][13][14], or as input for simplistic microstructural models [15][16][17]. An example of such a model, shown schematically in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The active cathode material has a stoichiometry of Ag 2 V 4 O 11 . 54 The cell reaction is defined as…”
Section: Medical Lithium Batteriesmentioning
confidence: 99%